Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3892/ijmm_00000159
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products regulate extracellular matrix protein and protease expression by human glomerular mesangial cells

Abstract: Abstract. Advanced glycation end products (AGEs) may play a role in the pathogenesis of diabetic nephropathy, by modulating extracellular matrix turnover. AGEs are known to activate specific membrane receptors, including the receptor for AGE (RAGE). In the present study, we analyzed the various receptors for AGEs expressed by human mesangial cells and we studied the effects of glycated albumin and of carboxymethyl lysine on matrix protein and remodelling enzyme synthesis. Membrane RAGE expression was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Another consideration needs to be kept in perspective for designing the AGE ligand as it relates to the ECM, since the latter undergoes notable transformation in the form of thickening of tubular basement membranes (TBMs) in tubulointerstitial in-jury in diabetic nephropathy (20). The major TBM or GBM proteins include type IV collagen and laminin, and the AGEs are known to modulate the turnover and expression of these ECM proteins and of proteases in glomerular cells, resulting in nodular sclerosis-a hallmark characteristic of diabetic nephropathy (5). In any instance, the glycated ligand of interest should have comparable binding affinity with RAGE as that of ECM proteins and S-100B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another consideration needs to be kept in perspective for designing the AGE ligand as it relates to the ECM, since the latter undergoes notable transformation in the form of thickening of tubular basement membranes (TBMs) in tubulointerstitial in-jury in diabetic nephropathy (20). The major TBM or GBM proteins include type IV collagen and laminin, and the AGEs are known to modulate the turnover and expression of these ECM proteins and of proteases in glomerular cells, resulting in nodular sclerosis-a hallmark characteristic of diabetic nephropathy (5). In any instance, the glycated ligand of interest should have comparable binding affinity with RAGE as that of ECM proteins and S-100B.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous past studies have used AGE-BSA to investigate the pathobiology of proximal tubules or tubulointerstitial compartment (17,31,36,44,57). The AGE-BSA also has been used to investigate mesangial cell biology, and in addition, its utility to study AGE-induced dysfunctions of endothelial and retinal pigment epithelial cells in vivo has been well described (5,11,50). The effect of AGE:RAGE interaction on cellular functionality was gauged by adherence assays, where it was noted that AGE-BSA increases adhesiveness of cells in a time-dependent manner with no effect on cell viability (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study to determine what is the transcriptomic response of mesangial cells to AGE during DN, microarray gene expression analysis revealed that in vitro propagation of human glomerular mesangial cells in a culture medium containing a high concentration of AGE leads to activation of expression of several genes involved in modulation of extracellular matrix turnover, including those encoding tPA, TIMP‐3 and PAI‐1. According to the authors, such changes in gene expression could trigger the inhibition of extracellular matrix remodelling and induction of glomerulosclerosis in kidney cells (Berrou et al, 2009). A role of RAGE/AGE signalling in acute kidney injury was explored in the study of Gerhardt and colleagues (2021), in which by combining single‐nucleus RNA‐seq with tracing of genetically labelled injured proximal tubule cells (PTCs), they revealed notable transcriptional activation of NF‐κB–, TNF‐ and activating protein‐1 (AP‐1)–signalling pathways in the PTCs during transformation after injury.…”
Section: Diaph1 Structure and Signalling Patternsmentioning
confidence: 99%